Peran Keraton Kasepuhan Cirebon Sebagai Pusat Pemeliharaan dan Pembangunan Budaya - Lestari, Dian; Kurnia, Heri; Ningtyas, Dina Nurayu; Khasanah, Isrofiah Laela (Academy of Social Science and Global Citizenship Journal, 2021)
Keraton Kasepuhan Cirebon plays a crucial role in preserving and developing the culture in the Cirebon region. Through traditional ceremonies, cultural performances, and cultural events, Keraton Kasepuhan Cirebon acts as a protector and catalyst for regional cultural life. Additionally, the palace also contributes to the promotion and development of cultural tourism, which boosts the local economy. In addition to preserving traditions and cultural arts, Keraton Kasepuhan Cirebon also serves as an institution for cultural education that encourages active participation from the community, especially the younger generation, in cultural activities. By teaching cultural values, the palace aims to preserve cultural heritage and foster a strong cultural awareness among the people. Overall, Keraton Kasepuhan Cirebon is a cultural center that plays a significant role in preserving, promoting, and developing the local culture in the Cirebon region. By serving as a hub for cultural nurturing and development, this palace contributes to enriching the local cultural identity, enhancing cultural awareness, and fostering sustainable regional development.